Metaphysics and Virtual Reality. Can the Universe and the Mind be Virtual Realities? - Liz, Manuel (Analysis. Journal of Philosophical Research, 2021)
New technologies are changing our world. And philosophy cannot keep out. Neither can its more speculative parts. In this paper, we analyze the notion of virtual reality in relation to four basic meanings. The virtual can be related with the idea of appearance, of potentiality, of mediation and of construction. In connection with that density of meaning, we explore a number of possibilities of virtuality for two limit cases: the Universe and the mind. And we argue for three important theses about virtual reality.